Effects of a Pre-surgery Supervised Exercise Training 1 Year After Bariatric Surgery: a Randomized Controlled Study - Baillot, Aurélie; Vallée, Carol-Anne; Mampuya, Warner M.; Dionne, Isabelle J.; Comeau, Emilie; Méziat-Burdin, Anne; Langlois, Marie-France (Obesity surgery, 2018)
Background We have previously reported on the benefits of Pre-Surgical Exercise Training (PreSET) on physical fitness and social interactions in subjects awaiting bariatric surgery (BS). However, data are needed to know whether these benefits are maintained post-BS. Objectives The purpose of this paper was to evaluate the effect of PreSET on physical activity (PA) level, physical fitness, PA barriers, and quality of life (QoL) 1 year (1-Y) after BS. Methods Of the 30 participants randomized into two groups (PreSET and usual care), 25 were included in the final analysis. One year after BS, time spent in different PA intensities and number of steps were assessed with an accelerometer. Before BS and until 1-Y after BS, physical fitness was assessed with symptom-limited cardiac exercise test, 6-min walk test (6MWT), and sit-to-stand, half-squat, and arm curl tests. QoL, PA barriers, and PA level were evaluated with questionnaires. Results The number of steps (7460 vs 4287) and time spent in light (3.2 vs 2.2 h/day) and moderate (0.6 vs 0.3 h/day) PA were higher in the PreSET group 1-Y after BS. The changes in 6MWT heart cost (1.3 vs 0.6 m/beats/min), half-squat test (38.8 vs 10.3 s), and BMI (− 16.8 vs − 13.5 kg/m 2 ) were significantly greater in the PreSET group compared to those in the usual care group. No other significant difference between groups was observed. Conclusion The addition of the PreSET to individual lifestyle counseling seems effective to improve PA level and submaximal physical fitness 1-Y after BS. Studies with larger cohorts are now required to confirm these results. The trial was registered at clinicaltrials.gov (NCT01452230).